Культурные идентичности: превращения и признания - Костенко, Н. (Социология: теория, методы, маркетинг, 2001)
Identity legitimacy is regarded as a key issue to understand the current post-communist world and to substantiate the identity recognition policy, that is a legitimate(for society) way of differentiation control. There are presented two ideal models of identity production: 1) based on essentialistic imperatives, and 2) close to con structivism in its various versions, like post-classical one. There are analyzed significant practices and figurative representations applied to identities.